Sound color in the music of Gyorgy Kurtag: String Quartet, Op. 1 / The sayings of Peter Bornemisza / Omagio a Luigi Nono / Messages of the Late R. V. Troussova - Iachimciuc, Igor (Saarbrücken Lambert academic publishing, 2010)
The music of György Kurtág is analyzed from the point of view of sound color. A brief description of what is understood by the term sound color, and various ways of achieving specific coloristic effects, are presented in the Introduction. An examination of Kurtágs approaches to the domain of sound color occupies the chapters that follow. Rather than relying on extended instrumental techniques, Kurtág creates a large variety of sound colors using traditional means such as pitch material, register, density, rhythm, timbral combinations, dynamics, texture, spatial displacement of the instruments, and the overall musical context. Each sound color unit in Kurtágs music is a separate entity, conceived as a complete microcosm. Sound color units can either be juxtaposed as contrasting elements, forming sound color variations, or superimposed, often resulting in a Klangfarbenmelodie effect. Some of the same gestural figures (objets trouvés) appear in different compositions, but with significant coloristic modifications. Thus, the principle of sound color variations is not only a strong organizational tool, but also a characteristic stylistic feature of the music of György Kurtág.Igor Iachimciuc received his Ph.D. in composition from the University of Utah. His awards include prizes in composition at the Silver Chrysanthemum (Moldova), and the 2003 Wayne Peterson's Prize (USA). Igor Iachimciuc's works have been performed by Ars Poetica, Earplay, New York, Canyonlands, and Flexible Music Ensembles.
A Dissertation submitted to the faculty of The University of Utah in partial fulfillment of the requirements for the degree of Doctor of Philosophy, 2010